Effectiveness of virtual fencing in a mountain environment and its impact on heifer behaviour and welfare - P. Fuchs; C.M. Pauler; M.K. Schneider; C. Umstätter; C. Rufener; B. Wechsler; R.M. Bruckmaier; M. Probo (Animal)
Virtual fencing (VF) could be beneficial in mountain areas where electric wire fencing is difficult and time-consuming. However, environmental challenges of mountain pastures may impair VF efficacy and functionality, with potential effects on animal behaviour and welfare. Thirty female heifers were equipped with activity sensors and VF collars to record activity behaviour, VF audio tones (ATs) and electric pulses (EPs). After VF training in the lowlands, the heifers were moved to a Swiss summer pasture. The mountain site was divided into nine paddocks, three of which were fenced with electric wire only (EF-only treatment) and six additionally used VF (VF treatment). During mountain grazing, the herd was split into three groups of 10 heifers each. All groups grazed simultaneously in separate paddocks and moved sequentially through the nine paddocks in a rotational grazing system. Video cameras recorded animal reactions upon virtual fence contact. Grass height was measured to estimate forage availability in the currently grazed paddocks. Data were analysed using mixed-effects models. From the activity data, we also calculated the Degree of Functional Coupling (DFC), a metric for examining circadian activity rhythms as an indicator of longer-term animal welfare, ranging from zero (poor) to one (good state of welfare). Throughout mountain grazing, we recorded 36 escaped animals in 11 events crossing an electric fence and 17 escaped animals in eight events linked to VF. Heifers received a mean (± SD) number of 5.9 ± 8.2 ATs and 0.3 ± 0.8 EPs per day. The ATs and EPs increased at lower grass heights (both P ≤ 0.004) and on days with unforeseen events (both P ≤ 0.001), such as encounters with wildlife or neighbouring cattle. Grazing interruptions associated with ATs were shorter during mountain grazing compared to VF training (P < 0.001). Fence type did not affect heifer step count (P > 0.05), but daily lying time was 10 min longer in the VF than EF-only treatment (P = 0.001). The heifer’s activity pattern was highly rhythmic at both fence types (DFC ≥ 0.92) but decreased during 7-d periods involving a paddock change within VF treatments (P < 0.001). In conclusion, the VF system was as reliable as electric fencing in preventing escape events. Heifers learned to respond appropriately to the VF stimuli, even in challenging mountainous terrain. An overall high activity rhythmicity reflected in the DFC supported that longer-term animal welfare was not compromised by VF use.